Pengaruh Konsentrasi POC limbah Kulit Jeruk Terhadap Pertumbuhan Tanaman Kangkung (Ipomoea reptans poir) Sebagai Rancangan Poster Biologi SMA Kelas XII - Nisa Rahmawati; Imam Mahadi; Wan Syafi’i (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
Abstract Orange peel waste is an organic waste containing essential nutrients such as nitrogen, phosphorus, and potassium, making it a potential raw material for Liquid Organic Fertilizer (LOF). This study aims to determine the effect of orange peel waste LOF concentrations on the growth of water spinach (Ipomoea reptans Poir) and to develop a learning media in the form of a poster for Grade XII high school biology on the topic of growth and development. The research was conducted from January to April 2025 in Tambang District and Binawidya Campus, Panam, using an experimental method with a Completely Randomized Design (CRD) consisting of five treatments (200 ml, 400 ml, 600 ml, 800 ml, and control), each replicated three times. Observed parameters included the number of leaves, plant height, root length, fresh weight, and dry weight. Data were analyzed using ANOVA followed by Duncan's Multiple Range Test (DMRT) at a 5% significance level. The results showed that the 600 ml LOF concentration had a significant effect on plant growth, particularly in the number of leaves, plant height, fresh weight, and dry weight, but had no significant effect on root length. The educational poster developed from the research findings was validated and deemed suitable as an alternative learning media in high school biology instruction.